Pengintegrasian Model Leadership Menuju Model yang Lebih Komprhensip dan Parsimoni - Miswanto Miswanti (Telaah Bisnis, 2016)
ABTSRACTThrough leadership models offered by Locke et. al (1991) we can say that whether good or not the vision of leaders in the organization is highly dependent on whether good or not the motives and traits, knowledge, skill, and abilities owned leaders. Then, good or not the implementation of the vision by the leader depends on whether good or not the motives and traits, knowledge, skills, abilities, and the vision of the leaders. Strategic Leadership written by Davies (1991) states that the implementation of the vision by using strategic leadership, the meaning is much more complete than what has been written by Locke et. al. in the fourth stage of leadership. Thus, aspects of the implementation of the vision by Locke et al (1991) it is not complete implementation of the vision according to Davies (1991). With the considerations mentioned above, this article attempts to combine the leadership model of the Locke et. al and strategic leadership of the Davies. With this modification is expected to be an improvement model of leadership is more comprehensive and parsimony.